Cross-Linguistic Influence in Indonesian-Dutch Bilingual Children: a Predictive Model - Irmawati, Mila; Paramarta, Bagus Pragnya (e-Journal of Linguistics; Vol 19 No 2 (2025): ejl-July, 2025)
Bilingualism is a common is common in many countries, retrieved by the existence of two languages within individuals. One notable challenge faced by bilinguals is the difficulty in expressing thought across languages since there will be an influence from one language to another; this phenomenon can be called a cross-linguistic influence (CLI). CLI arises from competition between languages, leading to interference that can manifest in various linguistic domains. Although CLI has been widely discussed in previous research, factors contributing to CLI are still debatable,  especially within the field of bilingualism.  The present study aims to predict the cross-linguistic interference between two different languages, Indonesian and Dutch. We examined this interference based on three hypotheses: Autonomous Development, Interface Hypothesis, and Competition Model. We use the descriptive qualitative method, we analyze the data extracted from bilinguals to test the validity of these hypotheses in predicting patterns of CLI between two varied language combinations. The result shows that the prediction regarding CLI is significantly determined by the typological distinction between Indonesian and Dutch. The study concludes that various predictions of cross-linguistic interference are related to the typological distinction between Indonesian and Dutch, as it is interpreted from those three frameworks. Finally, this study suggests that further research must evaluate and validate the prediction to gain a more in-depth understanding of theoretical and practical implications.